Implementation of corporate governance rules and procedures in lebanese firms - Elgammal, Walid (2014)
This study aims to evaluate the degree of disclosure implementation of corporate governance rules in developing/emerging nations by studying the Lebanese case. Few research works have been conducted regarding the implementation of corporate governance rules by Lebanese firms. The study includes a summary of past and current developments of corporate governance in emerging countries. In particular, it focuses on the important developments in Lebanon regarding the disclosure of corporate governance practices as well as the framework of regulatory practices, aiming to assess the score of corporate disclosure among leading Lebanese firms. Data for the study is generated through a questionnaire that complies with the United Nations corporate governance check-list. The questionnaire was distributed to a sample of managers of 30 leading Lebanese firms. The results of this research overlap with past researches done on emerging countries which suggest that the degree of corporate governance disclosure in these countries is relatively low, hence calling for more regulations-enforcement to the implementation of corporate governance rules. The results are significantly important indicators to the low level of implementation of corporate governance procedures in Lebanon. The study also highlights the low level of implementation of corporate governance rules in emerging countries other than Lebanon, and sheds light on the existence of a serious problem which is the deficiency of awareness in developing nations regarding the necessity and the benefits of corporate governance, added to a lack of regulatory agencies enforcing governance rules. The results suggest that, in order to enhance and improve the implementation level of corporate governance disclosures, Lebanese firms should increase the level of knowledge and education of corporate governance benefits, especially at the top management level. According to the Organization of Economic Cooperation and Development (OECD, 2004), corporate governance is defined as a system implemented in the company which guides and supervises the whole company. This system’s main function is to improve economic efficiency and growth. Proper corporate governance in a business leads to: increased investor’s confidence, organized set of relationships among the company's key elements such as shareholders, management, board of directors, and all stakeholders, and the achievement of goals. It also helps the organization to determine the means to achieve its objectives and monitor its performance. Moreover, good corporate governance practices take into account incentives and ensure that the company has an accountable board of directors and top management who work in the best interest of the company and its investors (Hashanah and Mazlina, 2005). The benefits of corporate governance of organizations in developing countries are many. If applied properly, corporate governance enhances growth rate and economic efficiency of the firms. Also, it increases the confidence level in the national economy and promotes economic growth. In addition to these, corporate governance emphasizes the protection of rights of minority shareholders against the majority (Dahawy, 2011). According to Morck and Steier (2005), when applied by companies, the accountability and transparency component of corporate governance would gain shareholders’ and investors’ trust. This is where corporate governance is of ultimate importance. Corporate governance is composed of several elements performing specific functions. The main elements are: audit committee, external auditor, internal audit, and board of directors. Corporate governance also takes into consideration other parties such as shareholders and all stakeholders (Staciokas & Rupsys, 2005). This research aims at exploring and evaluating the current degree of disclosure of corporate governance in Lebanon. Consequently, the purposes of this study are: 1) Present a summary of the most significant changes and framework of corporate governance of firms in developing/emerging countries. 2) Provide a summary of the most significant developments in Lebanon concerning corporate governance, including disclosure and framework. 3) Assess the outcomes obtained on the level of corporate governance disclosure practices and scores among 30 of the leading enterprises in Lebanon. Few research works have been conducted to study the disclosure degree of corporate governance in emerging economies. This leads to a serious problem which is the lack of knowledge and awareness of the advantages of corporate governance in such economies. Thus, there is a need to understand the framework and implementation of corporate governance in developing/emerging countries. There is no universal definition of corporate governance. The Institute of Internal Auditors (IIA) provided a more frequently used definition for governance considering it as the processes that the board uses to monitor and ensure the appropriate achievement of objectives (IIA, 2009). In order to ensure proper and sound corporate governance in a company, a coordinated relationship must exist among the several elements of corporate governance. The recent financial crisis and its implications have led developing nations to be highly interested in the framework of corporate governance in order to decrease their financial difficulties (Tsamenyi et al., 2007; Gugler et al., 2003; Rabelo & Vasconcelos, 2002; Reed, 2002; Ahunwan, 2002). Hoskisson et al. (2002) go further to show that different theoretical perspectives can provide useful insights into enterprise strategies in emerging economies. Rabelo and Vasconncelos (2002) claim that developing nations are different from developed nations regarding the elements that constitute corporate governance system and framework. The political and economic environments of developing nations are different than those of developed nations. A developing nation’s environment and economy are mostly characterized by a fragile legal system, state ownership, inefficient pool of human capitals, limited resource institutions, and small family owned businesses (Mensah, 2002; Young et al., 2008).